Penerapan Disiplin Waktu Kerja Karyawan Pada PT Gresik Migas - Rofiatul Fudlla Qurrota Ayun; Roziana Ainul Hidayati (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2023)
Good discipline reflects the magnitude of a person's sense of responsibility towards the tasks assigned to him. This encourages morale and the realization of company and employee goals. Therefore, every company will always try to make its employees have good work discipline, because good work discipline will greatly affect the progress of the productivity of the company's Human Resources. The purpose of this study is to determine the application of employee work discipline at PT Gresik Migas. This type of research is field research. This research uses inductive thinking methods. Data analysis techniques using interviews and documentation. The data sources in this study have two data sources, namely Primary Data and Secondary Data. The results of this study reveal that actually PT Gresik Migas has implemented work discipline, but employee performance has not met operational standards, because work discipline has not been fully implemented, there are some employees who have not comply with applicable regulations.